Interferensi Bahasa Ibu Oleh Guru dan Implikasinya Terhadap Bahasa Indonesia di SMP Negeri 13 Manado - Kumaat, Sylvia Ivone (Universitas Sam Ratulangi, 2018)
Language changes according to the influence of historical, psychological, social and cultural ( Hickerson 1980 : 5 ). Universality and diversity of language variation in terms of characteristics and functions of language can be observed in the school as an official institution in the field of education that organizes the learling process is considered as a small speech community or public education. As we know, school is a gathering place speakers who come from various backgrounds and different cultural communities. When the situation and conditions is the social interaction associated with the culture of each individual in the school, it appears that the communication that includes similarities and differences in the expression of speech of each individual. The core prolem in this reseach is the analysis the forms and causes interference language used by the teacher during the learning process takes place. The aims of this reseach were : identify and analyze the forms of interference mother language used by teacher.